Colonization dynamic and distribution of the endophytic fungus Microdochium bolleyi in plants measured by qPCR - Matušinsky, Pavel; Florová, Vendula; Sedláková, Božena; Mlčoch, Patrik; Bleša, Dominik (PloS one, 2024)
Microdochium bolleyi is a fungal endophyte of cereals and grasses proposed as an ideal model organism for studying plant-endophyte interactions. A qPCR-based diagnostic assay was developed to detect M. bolleyi in wheat and Brachypodium distachyon tissues using the species-specific primers MbqITS derived from the ITS of the ribosomal gene. Specificity was tested against 20 fungal organisms associated with barley and wheat. Colonization dynamics, endophyte distribution in the plant, and potential of the seed transmission were analyzed in the wheat and model plant B. distachyon. The colonization of plants by endophyte starts from the germinating seed, where the seed coats are first strongly colonized, then the endophyte spreads to the adjacent parts, crown, roots near the crown, and basal parts of the stem. While in the lower distal parts of roots, the concentration of M. bolleyi DNA did not change significantly in successive samplings (30, 60, 90, 120, and 150 days after inoculation), there was a significant increase over time in the roots 1 cm under crown, crowns and stem bases. The endophyte reaches the higher parts of the base (2-4 cm above the crown) 90 days after sowing in wheat and 150 days in B. distachyon. The endophyte does not reach both host species' leaves, peduncles, and ears. Regarding the potential for seed transmission, endophyte was not detected in harvested grains of plants with heavily colonized roots. Plants grown from seeds derived from parental plants heavily colonized by endophyte did not exhibit any presence of the endophyte, so transmission by seeds was not confirmed. The course of colonization dynamics and distribution in the plant was similar for both hosts tested, with two differences: the base of the wheat stem was colonized earlier, but B. distachyon was occupied more intensively and abundantly than wheat. Thus, the designed species-specific primers could detect and quantify the endophyte in planta.
Keywords: semena rostlinná; Ascomycota; Plant Leaves; Endophytes; Seeds; listy rostlin; endofyty